Aerological soundings of the surface boundary layer at Mizuho Station, East Antarctica - Kawaguchi, Sadao; Kobayashi, Shun'ichi; Ishikawa, Nobuyoshi; Ohata, Tetsuo (1982)
P(論文) Aerological soundings were carried out at Mizuho Station, East Antarctica as part of POLEX-South. Surface inversions were found on all soundings from the middle of March through the middle of October. The surface inversion thickness was not larger than 500m. The thickness under clear skies was larger than that under cloudy skies. Its intensity became stronger steadily from 3℃ in February to about 20℃ in May, and then weakend gradually from July to October under clear skies, intensity under cloudy skies was weaker than under clear skies, the difference being large in winter. The temperature difference of inversion top between strong and weak cases was small : the intensities of surface inversions were determined almost entirely by the surface temperatures. Wind speeds aloft increased with height from the surface to 150m, thereafter decreased to 900m height and then increased again. The wind direction turned counterclockwise with height so as to blow parallel to the contour line of the terrain in the lowest few hundred meters in about 60% of all cases. Not only the radiative heat loss but also the air advection from the interior is important in forming the surface inversion at Mizuho Station. The surface inversions here are destroyed not merely strong wind, but by the passage of synoptic scale disturbances. departmental bulletin paper